2014
DOI: 10.1038/ejhg.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for genetic testing for inherited retinal disease

Abstract: This paper investigates the willingness of adults with inherited retinal disease to undergo and pay for diagnostic genetic testing in three hypothetical scenarios and to explore the factors that influence decision making. Fifty patients were presented with three scenarios whereby genetic testing provided increasing information: confirming the diagnosis and inheritance pattern alone, providing additional information on future visual function, and identifying in addition a new treatment which could stabilise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Advances in genetic technology, particularly the development of next‐generation sequencing and the introduction of whole‐exome sequencing, will allow low cost, rapid and readily accessible genetic testing for rare conditions, such as IRD. Recent studies have demonstrated demand for such testing among adults with IRD . A potential benefit would be to allow affected individuals and their relatives to make informed reproductive choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in genetic technology, particularly the development of next‐generation sequencing and the introduction of whole‐exome sequencing, will allow low cost, rapid and readily accessible genetic testing for rare conditions, such as IRD. Recent studies have demonstrated demand for such testing among adults with IRD . A potential benefit would be to allow affected individuals and their relatives to make informed reproductive choices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated demand for such testing among adults with IRD. [1][2][3][4][5][6] A potential benefit would be to allow affected individuals and their relatives to make informed reproductive choices.…”
Section: Introductionmentioning
confidence: 99%
“…This study included responses that are provided in the context of individuals who actually received the service, in contrast to prior studies, which evaluated WTP for hypothetically receiving the service. [ 7 , 13 , 14 , 34 , 37 , 38 , 42 , 43 ] This testing may not be relevant to everyone of reproductive age, so while our study may not reflect the perspectives of the entire adult population, it is focused on an appropriate subset.…”
Section: Discussionmentioning
confidence: 99%
“…For many patients, this may represent their first experience receiving a clinical test in a pharmacy setting. Many patients may be more will ing to be tested since there is no cost, but studies have indicated patients' willingness to pay for genetic tests, particularly for older patients, with higher income and perceived clinical and personal utility [56][57][58][59]. A supplemental study to the proposed survey, such as a focus group study, may be of value to gather additional feedback from patients.…”
Section: Discussionmentioning
confidence: 99%